La imaginación en el espacio urbano de la narrativa de Luis Aguilar-Monsalve [Dossier: Más allá de la literatura: adaptaciones y nuevas formas de expresión cultural en Ecuador (Ponencias del Congreso de la Asociación de Ecuatorianistas, Quito, julio de 2019)] - Medina, Manuel F. (2020)
This article poses that the short fiction of Ecuadorian narrator Luis Aguilar Monsalve explores new ways of representing reality. His efforts result in a work on the fringe of the fantastic and the postmodern. A reader can see its narratological desire to step away from mere mimetic representation and successfully attempt to discover new ways of telling that evoke the use of simulacrum, virtual reality, and other models that question the persistence of real time. Within this framework, we find a predilection for narrating the city as a space where human beings often unsuccessfully struggle to communicate with each other in urban areas saturated with human traits and emotions.